Inclusive transport as a priority for European transport policy - Joanna Kos-Łabędowicz (Przegląd Europejski, 2023)
Transport accessibility, or rather the lack of it, increasingly referred to as transport exclusion or poverty, can lead to social exclusion and a range of negative social consequences. The aim of this article is to identify how accessibility and inclusiveness are treated in EU transport policies, in order to determine to what extent those policies are inclusive. The content analysis of EU transport policy documents issued between the years 2000 and 2022 will be conducted in this research. References to access and accessibility in the analysed documents consistently address mainly two issues: access for peripheral areas to the European transport system and ensuring accessibility of public transport. The second approach is relevant for ensuring the inclusiveness of the transport system.